Paleomagnetism of Precambrian Rocks of Laurentia - Irving, E.; Lapointe, P. (Geoscience Canada, 1975)
Summary If the paleomagnetic poies from the Grenville Province are excluded it is possible to construct a relatively simple path of apparent polar wander relative to the Precambrian shield of North America, Greenland, and NW Scotland ("- Laurentia) during the Proterozoic. This indicates (but does not prove) that during this time the main body of Laurentia has remained approximately intact and that the geosynclines in the Churchill Province were formed without large-scale (plate-style) dismemberment of Laurentia. Although it is possible to integrate the results from the Grenville into this path, it is not easy to do so, indicating that the southern part of the Grenville Province moved independently of the main body of Laurentia becoming sutured to it at -1000 my The path of apparent polar wandering can be divided into five tracks, providing a useful stratigraphie tool, and the data are consistent with Stockwell's stratigraphie scheme for the Proterozoic. Results from Sudbury indicate that the north range irruptive was horizontal when intruded.